A quorum-sensing molecule from Pseudomonas aeruginosa induces defensive multicellularity in a coinfecting pathogen - Stefan Katharios-Lanwermeyer; Tiffany M. Zarrella; Marshall Godsil; Stefanie Severin; Alejandro E. Casiano; Chin-Hsien Tai; Anupama Khare (Proceedings of the National Academy of Sciences, 2026)
Microorganisms commonly exist in polymicrobial communities, where they can respond to interspecies secreted molecules by altering behaviors and physiology; however, the underlying mechanisms remain underexplored. Here, we investigated interactions between Stenotrophomonas maltophilia and Pseudomonas aeruginosa , coinfecting opportunistic pathogens found in pneumonia and chronic lung infections, such as in cystic fibrosis. We found that S. maltophilia forms large protective multicellular aggregates upon exposure to P. aeruginosa secreted factors. Experimental evolution for lack of aggregation selected for fimbrial mutations and we found that fimbriae are required on both interacting S. maltophilia cells for aggregation. Untargeted metabolomics and targeted validations revealed that the quorum-sensing molecule Pseudomonas quinolone signal (PQS) directly induced S. maltophilia aggregation, and colocalized with the aggregates. Further, in coculture with P. aeruginosa , wild-type S. maltophilia formed aggregates, resulting in up to 75-fold increased survival from P. aeruginosa competition compared to fimbrial mutants. Finally, multiple other bacterial species similarly aggregated upon exposure to P. aeruginosa PQS, indicating a more general response. Collectively, our work identifies a multispecies interaction where a quorum-sensing molecule from a coinfecting pathogen is sensed as a “danger” signal, thereby inducing a protective multicellular response.